Standardized Telemedicine Software Development Kit with Hybrid Cloud Support - Jánki, Zoltán Richárd; Bilicki, Vilmos (Acta Cybernetica, 2024)
In modern Web development, it is expected that systems operating in the same area can be easily integrated. For common integration points, it is recommended to use a standardized data model and a common interface during the development as this will facilitate further integrations. The use of the cloud infrastructure is increasingly popular in telemedicine, but taking into account the goals, the productivity of the development, the availability of the system and the various regulations, choosing the right solution is not trivial. Inclouded platform consists of numerous currently active telemedical microservices that are working with a common software development kit. This tool provides a standardized data model for document-oriented database systems, has support for public and private clouds by using the classic Data Access Object (DAO) analogy and contains a lot of convenient functions as well. Furthermore, it is found that our solutions can significantly increase development productivity and is confirmed by measurements taken which involved software developers.